THE EFFECT OF OWNERSHIP AND CASH FLOW ON COMPANY VALUE WITH DEBT POLICY AS MEDIATION IN PHARMACEUTICAL COMPANIES - Rizki Realdi; Budi Alamsyah Siregar (SMBJ: Strategic Management Business Journal, 2022)
One of the impacts on economic growth is the increase in manufacturing companies. Manufacturing companies have an important role in the economic development of a country. This article discusses the scope of corporate value. The purpose of this article is to examine the effect of each variable on firm value & debt policy, as well as to examine the mediating variable. The population in this study was 11 companies. The sample in this study amounted to 8 pharmaceutical companies. This type of research is quantitative. The sampling method used in this study uses the purposive sampling method, which is based on certain considerations—data analysis using SPSS 25.00. The results of the study show that ownership has a significant effect of 0.009 <0.05 on debt policy. Cash flow and debt policy of 0.039 < 0.05. Ownership and firm value 0.000 < 0.05. Cash flow and firm value 0.869 > 0.05. Furthermore, debt policies do not mediate.